La interculturalidad como eje transversal en el proceso de enseñanza-aprendizaje en los estudiantes del cuarto año de la Unidad Educativa intercultural bilingüe “Gallo Rumi” sector rural Simiátug, provincia Bolívar. guía didáctica para la praxis cultural - Ruiz Caizaguano, Manuel (2017)
The objective of the present study is to develop a didactic guide to promote interculturality through the teaching process in the Bilingual Intercultural Educational Unit "Gallo Rumi" of the Simiátug Parish, where it is evident that the students come from different cultures and above all The teachers do not know the management and its treatment with regard to the interculturality, developing in them negative consequences in education and culture, reason why it has become a motive in the present investigation.